Strategies for defending a dribbler: categorisation of three defensive patterns in 1-on-1 basketball - Fujii, K.; Yamashita, D.; Yoshioka, S.; Isaka, T.; Kouzaki, M. (Sports Biomechanics, 2014)
To clarify the defending-dribbler mechanism, the interaction between the dribbler and defender should be investigated. The purposes of this study were to identify variables that explain the outcome (i.e. `penetrating` and `guarding`) and to understand how defenders stop dribblers by categorising defensive patterns. Ten basketball players participated as 24 dribbler-defender pairs, who played a real-time, 1-on-1 sub-phase of the basketball. The trials were categorised into penetrating trials, where a dribbler invaded the defended area behind the defender, and guarding trials, where the defender stopped the dribbler`s advance. Our results demonstrated that defenders in guarding trials initiated their movements earlier and moved quicker than the defenders in penetrating trials. Moreover, linear discriminant analysis revealed that the differences in initiation time and medio-lateral peak velocity between the defenders and dribblers were critical parameters for explaining the difference between penetrating and guarding trials. Lastly, guarding trials were further categorised into three process patterns during 1-on-1 basketball (i.e. `early initiation` trials, `quick movement` trials, and `dribbler`s stop` trials). The results suggest that there are three defending strategies and that one strategy would be insufficient to explain the defending-dribbler mechanism, because both players` anticipation and reactive movement must be considered.